Towards Estimating Rainfall Using Cellular Phone Signal - Low C.Y.; Solihin M.I.; Yanto; Ang C.K.; Lim W.H.; Hayder G. (Institute of Electrical and Electronics Engineers Inc., 2023)
Cellular telephones; Crowdsourcing; Learning systems; Machine learning; Regression analysis; Cellular Phone; Cellular signal data; Cellular signals; Crowd sourcing; Data preprocessing; Machine-learning; Pre-processing method; Rainfall estimations; Signal data; Signal level; Rain